Analisis Konsep Nurse Program Dalam Kerangka Intervensi Keperawatan Postpartum: Studi Berbasis Teori Cheryl Tatano Beck - Riah Damawanti; Imam Subiyono; Satriya Pranata; M. Fatkhul Mubin (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2025)
In-depth conceptual analysis of the NURSE Program (Nurturing, Understanding, Responding, Supporting, Empowering) intervention for postpartum depression based on Cheryl Tatano Beck's theory is still limited. To analyze and operationalize the NURSE concept into specific nursing actions and test its application in community public health center. Using sequential explanatory mixed methods. The qualitative phase involved concept analysis, followed by a quantitative quasi-experimental one-group pretest-posttest phase involving 30 postpartum mothers (EPDS ≥10) at the public health center. Data were analyzed descriptively and using paired t-tests. The analysis successfully mapped each NURSE concept to the stages of Beck's “Theory of Self-Loss.” The intervention showed a significant decrease in postpartum depression scores (p<0.001). The average EPDS score decreased from 17.2 (moderate-severe) to 8.6 (mild-non-depressed), with 83.3% of respondents experiencing a decrease in category. The NURSE Program is a coherent conceptual construct that integrates theory and is effectively applied. The results of this concept analysis can be used as standard operational guidelines for nurses in theory-based maternal mental health nursing care.